The The Barrier Factors to the Implementation of Building Information Modelling for Construction Industry in Sarawak - Jiong Ru Chan; Aidin Nobahar Sadeghifam; Meheron Selowara Joo (Tecno Scientifica Publishing, 2022)
Building Information Modelling (BIM) Construction Lifecycle Process offers digital construction solutions throughout the whole project lifecycle by providing sustainable productivity and quality and increasing the work collaboration and efficiency of the design teams. BIM represents the development and application of computer-generated n-dimensional (n-D) models to simulate building construction planning, design, construction, and operation. In Sarawak, the BIM technology does not meet the construction stakeholder's expectations during the project lifecycles in different stages, which resulted in low BIM implementation. Therefore, this research study aims to identify the salient barrier factors to the implementation of BIM in the Sarawak construction industry, specifically in the design stage. To achieve the research study, the methodology is applied through literature review, followed by an online interview with BIM experts in Sarawak Construction Industry. Lastly, the findings of this study indicate the most salient factors faced by the Sarawak construction industry until the present, in terms of Technology, Cost, Management, Personal and Policy, such as (1) Lack of active participation from consultants in the project team, (2) Low enforcement from client, (3) Lack of senior management support, (4) Lack of desire to change of the older generation to implement BIM and (5) Lack of the knowledge regarding the cost benefits for implementing BIM.